Differential Proteomic Analysis of the Hippocampus in Rats with Neuropathic Pain to Investigate the Use of Electroacupuncture in Relieving Mechanical Allodynia and Cognitive Decline - Degui Gong; Xiangmei Yu; Menghong Jiang; Changzheng Li; Zhifu Wang (Neural Plasticity)
Abnormal changes in hippocampal function and neuroplasticity are involved in neuropathic pain, which induces hyperalgesia and learning and memory deficits. Previous studies from our group have shown that electroacupuncture at Huantiao (GB30) and Yanglingquan (GB34) has an obvious analgesic effect on neuropathic pain. However, the central regulatory mechanism occurring in the hippocampus remains to be investigated. In this study, behavioral and proteomic analyses were performed to identify differentially expressed hippocampal proteins involved in electroacupuncture-induced analgesia. Our results showed both upregulated (TMEM126A, RDH13, and Luc7L) and downregulated proteins (Mettl7A, GGA1 RTKN, RSBN1, and CDKN1B). Further protein verification revealed for the first time that hippocampal TMEM126A plays an important anti-inflammatory role in the treatment of neuralgia by electroacupuncture.